Heat transfer augmentation of heated block surfaces in a turbulent flow channel by a slotted ribbed plate. (16th November 2020) - Perng, Shiang-Wuu; Wu, Horng-Wen; Hsu, Chen-Hua; Hung, Ying-Sheng
Abstract: This numerical study performed the three-dimensional simulations to explore the turbulent thermal flow characteristics over the heated blocks inside a square channel by a slotted ribbed plate through the RNG κ − ε turbulence model and SIMPLE-C algorithm. The influence of slotted ribbed plate on the enhancement of turbulent heat transfer from these heated block surfaces would be evaluated through varying the pitch ratio of rib (1.2, 0.8, and 0.6) and the streamwise locations of slotted ribbed plate (before the left side of first heated block, x  = 130 mm; aligned with the left side of first heated block, x  = 150 mm; after the left side of first heated block, x  = 170 mm) under different Reynolds numbers (5000, 6500, 8000, and 9500). The results of numerical analyses reveal that the slotted ribbed plate placed above the heated blocks can effectually augment the heat transfer. In addition, these slots can induce the local fluid flow bursts along the surfaces of the blocks and modify flow interaction between the ribs and blocks on a channel. The slotted ribbed plate aligned with the left side of first heated block can lead to greater overall-mean Nusselt number than the other locations. As compared to C0 (without plate), C5 (the slotted ribbed plate of 0.8 pitch ratio located at x  = 150 mm) brings the maximum enhancement ratio of the overall-mean Nusselt number about 1.57 at Re = 9500. Under considering the friction through the channel, C7 (the slotted ribbed plate of 0.6 pitch ratio located at x  = 130 mm) gains the best thermal performance factor about 1.45 at Re = 5000.